2016
DOI: 10.1002/pbc.26351
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II trial of AT9283, a selective inhibitor of aurora kinase in children with relapsed or refractory acute leukemia: challenges to run early phase clinical trials for children with leukemia

Abstract: Aurora kinases regulate mitosis and are commonly overexpressed in leukemia. This phase I/IIa study of AT9283, a multikinase inhibitor, was designed to identify maximal tolerated doses, safety, pharmacokinetics, and pharmacodynamic activity in children with relapsed/refractory acute leukemia. The trial suffered from poor recruitment and terminated early, therefore failing to identify its primary endpoints. AT9283 caused tolerable toxicity, but failed to show clinical responses. Future trials should be based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…A greater understanding of the development and progression of pediatric disease is crucial for optimizing study designs for control groups, stratification, and biomarker assay development. The observation that activity of an agent in pediatric leukemia may be limited to patients with specific mutations (38), or Rb status in solid tumors (16), would require recruitment of select patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater understanding of the development and progression of pediatric disease is crucial for optimizing study designs for control groups, stratification, and biomarker assay development. The observation that activity of an agent in pediatric leukemia may be limited to patients with specific mutations (38), or Rb status in solid tumors (16), would require recruitment of select patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Other toxicities were fatigue, infections, febrile neutropenia and increased alanine transaminase. The phase I/II trial of AT9283 for relapsed/refractory acute leukemia (NCT01431664) did not accomplish the primary endpoint of identifying a dose for phase II assessment (38). This study was terminated because there was no evidence of clinical efficacy for the doses examined.…”
Section: Aurora Kinase Inhibitionmentioning
confidence: 99%
“…The aim in the study reported by Vormoor et al. was to recruit 12–18 patients over three dose levels starting at a relatively low dose of 9 mg/m 2 /day, which is only approximately 10% of the maximum tolerated dose (MTD) in adult hematological malignancies (108 mg/m 2 /day, with cardiac safety signals at the MTD) . In the adult phase I study, some data were provided on phosphorylation of the aurora kinase B substrate phospho‐histone H3, which were however incomplete .…”
mentioning
confidence: 88%
“…In addition, most patients are heavily pretreated by the time they are eligible for a phase I study, which may lead to organ toxicity and screen failures. This has clear logistical implications for the number of study center sites and countries that are needed to successfully complete such a trial: four centers in one country only – as attempted in the AT9283 study – do not longer suffice. For this reason, over the past decade, the Innovative Therapies for Children with Cancer consortium (http://www.itcc-consortium.org) developed a site network, now comprising 51 sites, with the aim to increase capacity (and quality) when it comes to delivering early phase studies in children with cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation